Evaluasi Kapasitas Eksisting Sungai Batang Mangor di Hulu Bendung Ladang Laweh Dengan Peningkatan Debit Banjir Rencana 25 Tahun - Hartati, Hartati; Dalrino, Dalrino; Sari, Desnila; Mafriyal, Mafriyal; Hanwar, Suhendrik; Sadtim, Sadtim; Desvani, Maulia; Putri, Nadhia Hanifah (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Ladang Laweh Irrigation District Dam is located in Sicincin nagari, Padang Pariaman Regency with an irrigation service area of 1,140 Ha. The Ladang Laweh Irrigation Area weir receives flow from the Batang Mangor river which is included in the Batang Mangor watershed. On September 22, 2021 a flood occurred on September 22, 2021 resulting in an overflow with a height of 2.5 m above the lighthouse with an estimated discharge of 141.946 m3 /dt resulting in runoff flow in the area upstream of the bending. Analysis of the capacity of the existing river upstream of the weir was carried out with a 25-year plan flood discharge. Modeling is done by analyzing 15 years of rain data and catchment area starting from the location point of the weir upstream. The validation results under full bank capacity conditions obtained the closest match to the theoretical flood discharge value of the Nakayasu method. The simulation results show that the existing cross section of segments P1 to P19 at the Korong Gadang location is inundated during flood events with river capacity in several locations exceeding the maximum capacity. The results also provide recommendations for flood management by suggesting the addition of river embankments at locations that experience inundation.